BRIGHT AFTER RAIN - Muhammad Ikhwandi; Erfan Erfan; Esy Maestro (FBS Universitas Negeri Padang, 2018)
AbstractThis work aims to express the life story of the education (lectures), the writer who at first only thought that entering the world of education (lectures) was only for fun and just going along, only for riots and never thinking about the real life (the future), and eventually, the writer was aware and got motivation from within his subsconsciousness after seeing the results of the struggle of other people or friends of the writer himself. Then, from the motivation that had been gained, the author expressed and conveyed a flashback of his life which at first was very happy and proud because he had entered the world of lectures, lived days full of joy and riots so he forgot his own responsibilities as a student. The writer who was complacent about the life he lived in. Finally the writer was aware and also motivated to be able to achieve what has been achieved by other people or friends of the author expresses some kinds of atmosphere such as happiness, tense, sadness/repentance, and end with a feeling of emotion of true happiness through musical composition. The idea of this work began with the writer's mood in each of its parts.Keywords: Bright After Rain